Linear-based Newton-Raphson Approximation for Power Flow Solution in DC Power Grids (2018)
This paper presents a linear-based Newton method for load flow solution in DC power grids. This approximation is based on the classical Taylor's series expansion combined to the open-circuit voltage obtained when all the constant power load points are disconnected. This solution strategy avoids the usage of an iterative process to solve the load flow problem in DC power grids reducing its processing time. Notwithstanding its simplicity, the proposed method is very accurate when is compared to classical Gauss-Seidel or Newton-Raphson methods concerning the solution quality. Simulation results are conducted via MATLAB software by using two radial test feeders composed by 10 and 33 nodes reported in the specialized literature. © 2018 IEEE.